Achieving successful community engagement: a rapid realist review - E. De Weger; N. Van Vooren; K. G. Luijkx; C. A. Baan; H. W. Drewes (BMC, 2018)
Abstract Background Community engagement is increasingly seen as crucial to achieving high quality, efficient and collaborative care. However, organisations are still searching for the best and most effective ways to engage citizens in the shaping of health and care services. This review highlights the barriers and enablers for engaging communities in the planning, designing, governing, and/or delivering of health and care services on the macro or meso level. It provides policymakers and professionals with evidence-based guiding principles to implement their own effective community engagement (CE) strategies. Methods A Rapid Realist Review was conducted to investigate how interventions interact with contexts and mechanisms to influence the effectiveness of CE. A local reference panel, consisting of health and care professionals and experts, assisted in the development of the research questions and search strategy. The panel's input helped to refine the review's findings. A systematic search of the peer-reviewed literature was conducted. Results Eight action-oriented guiding principles were identified:Ensure staff provide supportive and facilitative leadership to citizens based on transparency;foster a safe and trusting environment enabling citizens to provide input;ensure citizens' early involvement;share decision-making and governance control with citizens;acknowledge and address citizens' experiences of power imbalances between citizens and professionals;invest in citizens who feel they lack the skills and confidence to engage;create quick and tangible wins;take into account both citizens' and organisations' motivations. Conclusions An especially important thread throughout the CE literature is the influence of power imbalances and organisations' willingness, or not, to address such imbalances. The literature suggests that 'meaningful participation' of citizens can only be achieved if organisational processes are adapted to ensure that they are inclusive, accessible and supportive of citizens.